Liquidity and Leverage Impact on Islamic Bank Value: A Test on Multigroup Moderated Mediation Effect - Ahmad, Yusuf Falaqi; Ekowati, Vivin Maharani; Meldona (Journal of Islamic Economics and Finance Studies, 2025)
Firm value is a critical indicator for evaluating a company's performance and future prospects in the market. Factors such as liquidity, leverage, and dividend policy can influence firm value, particularly in the Islamic banking sector, which is characterized by distinct financial management principles. This study aims to examine the impact of liquidity and leverage on firm value, with profitability serving as a mediating variable and dividend policy as a moderating variable. The analysis focuses on Islamic Commercial Banks in Indonesia, Pakistan, and Bangladesh over the period 2019–2023. A quantitative research approach is employed, utilizing Moderated Regression Analysis (MRA) and Path Analysis. The sample comprises financial statement data from Islamic Commercial Banks in the three countries. The independent variables are liquidity, measured by the Current Ratio (CR), and leverage, measured by the Debt to Equity Ratio (DER). The dependent variable is firm value, proxied by the Price to Book Value (PBV). Profitability, measured by Return on Assets (ROA), functions as the mediating variable, while the Dividend Payout Ratio (DPR) represents the moderating variable. he findings reveal that both liquidity and profitability have a significant positive effect on firm value, while leverage exerts a significant negative effect. Profitability mediates the relationship between leverage and firm value but does not mediate the relationship between liquidity and firm value. Additionally, dividend policy does not moderate the effect of either liquidity or leverage on firm value. These results suggest that Islamic bank management should prioritize enhancing liquidity and profitability to improve firm value, while also exercising caution in managing leverage due to its adverse impact. Furthermore, as dividend policy does not function effectively as a moderating mechanism, strategies aimed at increasing firm value should focus more on strengthening fundamental financial performance.